Empowering Future Nurses: Overcoming Challenges and Embracing the Benefits of Research in Nursing Education. - Riaz, Stephen (International Journal of Endorsing Health Science Research, 2023)
Nursing education involves extensive training to develop critical thinking and decision-making skills that are essential for effective patient care. Research is a crucial component of nursing education as it provides opportunities for students to gain new knowledge and apply evidence-based practices. However, undergraduate nursing students often view research as a challenging and intimidating task. Negative perceptions and lack of resources and support can hinder students' ability to conduct research successfully. This article emphasizes the importance of research in nursing education and highlights the challenges that undergraduate nursing students face when conducting research. It also explores ways in which nursing schools can provide necessary resources and support to overcome these challenges and help students develop research skills. By doing so, nursing students can become more confident and effective practitioners based on evidence-based practice, contributing to better patient outcomes.